Effects of addition of rituximab to chemotherapy on central nervous system events in patients with diffuse large B-cell lymphoma - LAW, MAN FAI (Mol Clin Oncol, 2015)
The aim of this study was to evaluate whether the addition of rituximab to chemotherapy reduces central nervous system (CNS) events and to identify the risk factors associated with CNS involvement. Patients who were diagnosed with diffuse large B-cell lymphoma (DLBCL) between January, 1995 and December, 2012, without prior CNS disease, were recruited in this study. The patients received chemotherapy with cyclophosphamide, doxorubicin, vincristine and prednisolone (CHOP) or CHOP with rituximab (R-CHOP), with curative intent. The incidence rate of subsequent CNS events was compared between the two groups. A total of 110 patients were recruited, 45 (41%) of whom received CHOP and 65 (59%) R-CHOP. A total of 12 patients (10.9%) subsequently exhibited CNS involvement. The median time from the initial DLBCL diagnosis to CNS disease was 6.7 months (range, 1.3–23.8 months). The CNS disease rate was 15.5% (7/45) in the CHOP group vs. 7.6% (5/65) in the R-CHOP group. The projected 3-year CNS disease rate was 18% in the CHOP group vs. 9% in the R-CHOP group (P=0.15). The survival of patients with CNS disease was poor, with a median survival of 5.8 months. On multivariate analysis using the Cox proportional model, stage IV disease remained an independent predictor of CNS disease (hazard ratio = 7.75, 95% confidence interval: 1.67–35.92, P=0.009). In conclusion, the addition of rituximab to chemotherapy did not appear to reduce the risk of CNS events in our study. Other effective prophylactic measures are required to reduce the incidence of CNS events. High-dose intravenous methotrexate crosses the blood-brain barrier and may be used as CNS prophylaxis in high-risk patients.